2023
DOI: 10.1039/d2fo02722d
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from the seeds of Gleditsia sinensis Lam. attenuate DSS-induced colitis in mice via improving gut barrier homeostasis and alleviating gut microbiota dybiosis

Abstract: The polysaccharides from seeds of Gleditsia sinensis Lam. alleviate DSS-induced colitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The sequences of the gene-specific primers used in the experiment are shown in Table 1. 49,50 Statistical Analysis. In this study, all data are shown as mean ± standard deviation (SD) from three independent measurements (n = 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the gene-specific primers used in the experiment are shown in Table 1. 49,50 Statistical Analysis. In this study, all data are shown as mean ± standard deviation (SD) from three independent measurements (n = 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The 2 –ΔΔCt method was used to calculate the relative expression level of all target genes, and glyceraldehyde-3-phosphatase dehydrogenase (GAPDH) was used as a normalized control. The sequences of the gene-specific primers used in the experiment are shown in Table . , …”
Section: Methodsmentioning
confidence: 99%
“…Then, the sections were stained using hematoxylin and eosin, and the resulting stain observations were photographed and analyzed with an inverted microscope. The detection of the tight junction protein (ZO-1) in colonic tissues was conducted through immunohistochemistry [26]. The fixed colon tissue was sectioned and dewaxed, and then the antigen repair and BSA closure were performed.…”
Section: Hematoxylin and Eosin (Hande) Staining And Immunofluorescenc...mentioning
confidence: 99%
“…The intestine is the largest barrier between organisms and environment, protecting the body from harmful external substances. The intestinal barrier mainly consists of four parts, namely physical, chemical, immunological, and microbiological barriers, among which the physical barrier is an intact intestinal epithelium structure consisting of intestinal mucosal epithelial cells through tight junction proteins, such as occludin, claudins, zonula occludens (ZOs), and tricellulin [8,9]. Food, especially high-fat and high-fructose food, can cause great damage to the intestinal barrier [10].…”
Section: Introductionmentioning
confidence: 99%